Temuan Keratocyst Odontogenic Tumor besar pada maksila pada pemeriksaan CBCT - Berty Pramatika; Suhardjo Sitam; Ria Noerianingsih Firman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2019)
Objectives: The aim of this case report is to describe radiographic characteristic of keratocyst odontogenic tumor (KCOT) in maxilla using CBCT. Case Report: A 20 year-old women patient was referred to the Oral Maxillofacial Radiology Department of Padjadjaran University with the chief complaint of swelling, painless in the anterior of the upper jaw. In this presented case, we used cone beam computed tomography (CBCT) to find out the margin of the cortical extension, and diameter of the lesion. The CBCT examination shows radiolucent, well-defined lesion in 12-14 region with displacement of 12. The size of the lesion is about 20x15x19mm extended posterior-superiorly near to nasal cavity and it shows less degree of bone expansion. Based on radiographic and clinical examination, the diagnosis was keratocyst odontogenic tumor (KCOT). Conclusion: KCOT has some radiographic characteristic distinguishable with another odontogenic lesion. Therefore, CBCT examination is recommended for the diagnosis of odontogenic keratocyst and proper surgical planning.